Morphological characteristic of dengue vectors Aedes aegypti and Ae. albopictus (Family: Culicidae) using advanced light and scanning electron microscope - SUPRIYONO SUPRIYONO; SUSI SOVIANA; MUHAMMAD FALIKHUL MUSYAFFA; DIMAS NOVIANTO; UPIK KESUMAWATI HADI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Supriyono, Soviana S, Musyaffa MF, Novianto D, Hadi UK. 2023. Morphological characteristic of dengue vectors Aedes aegypti and Ae. albopictus (Family: Culicidae) using advanced light and scanning electron microscope. Biodiversitas 24: 894-900. Dengue infection is still a major public health problem in Indonesia, with Aedes aegypti and Aedes albopictus as vectors. This study aims to determine the description characteristics of these mosquitoes using an advanced light microscope and scanning electron microscope (SEM). The adult mosquitoes of Ae. aegypti and Ae. albopictus were collected from Darmaga, Bogor, in 2021. Ae. aegypti has a brown to dark body color with sub median white line like a lyre-shaped on the mesonotum, dark proboscis, a white knee spot on the femora, mid femur with a longitudinal white stripe, and mesepimeron with two well-separated white scale patches. Ae. albopictus has dark body color, dark proboscis, white strip on the middle of mesonotum, and not separated white scale patches on the mesepimeron and mid femur without a longitudinal white stripe. SEM showed the characteristic microstructure of Ae. aegypti and Ae. albopictus did not have a significant difference. Several sensory organs, namely funiculus, microtrichia, and trichoidea, are distributed on the proboscis, palps, and antennae. Microtrichia is spread almost all over the body, especially the palps, proboscis, thorax, and abdomen. This research is important for basic information to develop effective and efficient mosquito vector control strategies.